FACTORS INFLUENCING ACADEMIC FRAUD BASED ON THE FRAUD DIAMOND THEORY OF ECONOMICS EDUCATION STUDENTS AT JAKARTA STATE UNIVERSITY - Ristiana, Ayu; Mukhtar, Saparuddin; Sariwulan, Rd. Tuty (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study was conducted to determine the influence of pressure, opportunity, rationalization, and capability on academic fraud of economic education students at State University Jakarta. The method used is quantitative with a causal approach. The sampling technique in this study was nonprobability sampling with accidental sampling type and hypothesis testing using multiple linear regression analysis. Respondents in this study were Economics Education students at the State University of Jakarta, semester IV and semester VI, totaling 129 students. The results showed that pressure, rationalization, and capability positively and significantly affected academic fraud, while the opportunity factor had no positive or significant effect